INTEGRASI PENDEKATAN GROUP INVESTIGATION DALAM MENINGKATKAN HASIL BELAJAR GEOGRAFI DI SMAN - Umsiyah Umsiyah; Ketut Prasetyo; Sukma Perdana Prasetya (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This study aims to analyse the application of the group investigation (GI) approach method in improving the analysis skills of population mobility in Indonesia in geography learning class XI IPS at SMA Negeri 1 Ngraho. This study uses a quantitative approach with a pretest-postttest control group design, research data obtained through classroom action research conducted at SMA Negeri 1 Ngraho, Bojonegoro. The results showed that the GI method significantly improved analytical skills, with scores increasing from 60 initially to 68 in cycle I, 75 in cycle II, and 82 in cycle III. This shows its effectiveness in helping students understand migration, urbanisation and population distribution. GI also enhances social skills such as communication, collaboration and leadership. Despite initial challenges such as limited understanding of the method and discussion time, the students became increasingly engaged. This research underlines GI as an innovative approach to improving analytical skills in geography education.